2022
DOI: 10.3390/rs14153695
|View full text |Cite
|
Sign up to set email alerts
|

Constructing High-Resolution (10 km) Daily Diffuse Solar Radiation Dataset across China during 1982–2020 through Ensemble Model

Abstract: Diffuse solar radiation is an essential component of surface solar radiation that contributes to carbon sequestration, photovoltaic power generation, and renewable energy production in terrestrial ecosystems. We constructed a 39-year (1982–2020) daily diffuse solar radiation dataset (CHSSDR), using ERA5 and MERRA_2 reanalysis data, with a spatial resolution of 10 km through a developed ensemble model (generalized additive models, GAM). The validation results, with ground-based measurements, showed that GAM had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 68 publications
1
1
0
Order By: Relevance
“…Similar underestimates of the DHI irradiances and overestimates of the DIRhor irradiances are found for all of the SURFRAD, SOLRAD, and ARM-SGP sites. We note that Wu et al [17], Jiang et al [18], and Li et al [19] also found similar opposing diffuse and direct beam biases in the ERA5 in China, demonstrating the consistency of these errors across diverse geographic regions.…”
Section: Evaluation and Bias Correction Of Era5-derived Solar Capacit...supporting
confidence: 68%
See 1 more Smart Citation
“…Similar underestimates of the DHI irradiances and overestimates of the DIRhor irradiances are found for all of the SURFRAD, SOLRAD, and ARM-SGP sites. We note that Wu et al [17], Jiang et al [18], and Li et al [19] also found similar opposing diffuse and direct beam biases in the ERA5 in China, demonstrating the consistency of these errors across diverse geographic regions.…”
Section: Evaluation and Bias Correction Of Era5-derived Solar Capacit...supporting
confidence: 68%
“…Fewer studies have evaluated the solar direct and diffuse components of downward solar irradiance, which are required for calculating solar power on tilted panels. Using a network of 17 stations in China, Wu et al [17] found that the ERA5 underestimates the diffuse irradiance, while Jiang et al [18], using an observation network of 39 stations in China, found that the ERA5 underestimates diffuse radiation by 43 Wm −2 , but overestimates the direct radiation by 74 Wm −2 . Using observations from 14 stations, Li et al [19] also found a negative ERA5 bias for diffuse irradiance, and a positive bias for the direct beam, and concluded that, in addition to cloud effects, at least part of these biases can be attributed to aerosols.…”
Section: Introductionmentioning
confidence: 99%